The study of laser drilling of polymeric material - Mohd Khairi Azri, Shapie (2013)
Polymeric materials is widely used in many applications due to its advantages character but unfortunately, this polymeric material are fragile and not rigid for their manufacturing process. In order to overcome this problem, the non-contact laser drilling process is the best solution. However, poor quality of drill has been rise as critical issues in industry due to the improper setting of drilling parameters. The purpose of this study are to study the possibilities of low power laser on drilling polymeric materials and to identify the optimum parameters in order to obtain a good geometry of drill hole. There were three different test to be analysed in this analysis that are depth, kerf width and angle for the laser drilling process. A polymeric specimen with the thickness of 3 mm were used in this analysis. The Taguchi method has been applied in this analysis. The results show that the optimum parameter for the standoff distance is 34 mm while for the optimum drilling time is 10 s is needed for the depth, kerf width and angle analysis for obtain the best geometry of the hole. Confirmation test has been done to prove this findings. It is proved that a low power laser drill machine can be used to drill the polymeric materials and the parameters stated were the optimum parameters to be used in order to obtain a good geometry drill hole